(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The task of determining the level of intelligence has been one of the most important tasks in psychology since the formation of this science. The intellectual index of this person made it possible to describe his mental and moral qualities. Determining the quantitative and qualitative relationship of these indicators to the level of mental development made it possible to develop various methods of studying intelligence and related qualities. Assessment of abilities of preschool children and developmental trends in IQ scores.